2015
DOI: 10.1039/c5cp02083b
|View full text |Cite
|
Sign up to set email alerts
|

Can inorganic salts tune electronic properties of graphene quantum dots?

Abstract: Electronic properties of graphene quantum dots (GQDs) constitute a subject of intense scientific interest. Being smaller than 20 nm, GQDs contain confined excitons in all dimensions simultaneously. GQDs feature a non-zero band gap and luminescence on excitation. Tuning their electronic structure is an attractive goal with technological promise. In this work, we apply density functional theory to study the effect of neutral ionic clusters adsorbed on the GQD surface. We conclude that both the HOMO and the LUMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Among these applications, ions or hydrated ions adsorption on graphene surfaces plays an important role in both regulating the properties of graphene and controlling the relevant process behavior. For example, the adsorption of monovalent ion can engineer the electrical properties of graphene systems through changing the band‐gap ,. More recently, it was found that, hydrated ion adsorption on the interfaces between electrolyte and graphene surfaces can control the transport and selectivity in graphene‐based nanofluidics devices and processes, which also have promising applications in membrane‐based power generation ,.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these applications, ions or hydrated ions adsorption on graphene surfaces plays an important role in both regulating the properties of graphene and controlling the relevant process behavior. For example, the adsorption of monovalent ion can engineer the electrical properties of graphene systems through changing the band‐gap ,. More recently, it was found that, hydrated ion adsorption on the interfaces between electrolyte and graphene surfaces can control the transport and selectivity in graphene‐based nanofluidics devices and processes, which also have promising applications in membrane‐based power generation ,.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the adsorption of monovalent ion can engineer the electrical properties of graphene systems through changing the band-gap. [4,5] More recently, it was found that [6,7] hydrated ion adsorption on the interfaces between electrolyte and graphene surfaces can control the transport and selectivity in graphenebased nanofluidics devices and processes, which also have promising applications in membrane-based power generation. [8,9] All these novel applications require precise understanding of the interaction between ions and graphene surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Anions are always concomitant with metal ions and are indispensable components of salt solutions. In contrast to the studies focusing on metal ions, few reports have been made with respect to anions . Edge functionalization is a facile and effective method to regulate the electronic properties of graphene by affecting the π conjugation and charge distribution .…”
Section: Introductionmentioning
confidence: 99%
“…Circumcoronene (CC) is a polyaromatic hydrocarbon composed of 54 carbon atoms arranged in 19 hexagonal rings. It has been previously used as a model system of the graphene quantum dot (GQD), [20,22,29,30,[38][39][40][41] because it has a high symmetry and sufficient yet reasonable size from the computational point of view. Optimized geometries (B3LYP/6-311G* level of theory) of Cu-doped and Cu-decorated CC were taken from authors' previous works, [20,22] considering only the most stable positions of dopant or decorating Cu atom.…”
Section: Computational Detailsmentioning
confidence: 99%